Homoharringtonine Exerts an Antimyeloma Effect by Promoting Excess Parkin-Dependent Mitophagy - Zhang Y; Huang N; Xu J; Zheng W; Cui X (Dove Medical Press, 2020)
Yanyu Zhang,1 Ning Huang,2 Jie Xu,3 Wei Zheng,3 Xing Cui3 1Department of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 2Clinical Laboratory Department, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 3Department of Hematology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of ChinaCorrespondence: Xing CuiDepartment of Hematology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong Province 250014, People’s Republic of ChinaTel/Fax +86 68616042Email cdz45@foxmail.comPurpose: Homoharringtonine (HHT) has been used as an antileukemia agent in the clinic which processes a high-potential therapeutic efficacy against multiple myeloma (MM). In this study, we investigated the antimyeloma mechanism of HHT.Methods: Three MM cell lines and a xenograft model were applied. Mitochondrial function was evaluated by detecting MitoTracker Green, the mtDNA copy number, mitochondrial protein and enzyme activity, the mitochondrial membrane potential and mitochondrial morphology. Mitophagy levels were assessed by monitoring autophagosomes, performing a colocalization analysis and determining the levels of related proteins. An shRNA was applied to knockdown Parkin.Results: Based on the results of the in vitro experiments, HHT exerted a promising antiproliferative effect on the MM.1S, RPMI 8226 and H929 cell lines by increasing mitophagy. In addition, HHT markedly inhibited myeloma tumor growth and prolonged survival by promoting mitophagy in vivo. Furthermore, HHT treatment contributed to notable mitochondrial dysfunction and Parkin-dependent mitophagy, as evidenced by the destruction of mitochondria, the decrease in the mtDNA copy number, decrease in the Bcl-2/Bax ratio, and decrease in the levels of mitochondrial proteins and the optimal expression of Parkin and NDP52. However, the addition of rapamycin did not produce significant synergistic effect with HHT, indicating that HHT reached the threshold level to induce mitophagy. The colocalization analysis and assessment of mitochondrial function examination further confirmed that HHT triggered mitophagy and mitochondrial dysfunction. Moreover, the antiproliferative effect of HHT was reversed by an shRNA targeting Parkin, highlighting the indispensable role of Parkin-dependent mitophagy in the antimyeloma effect of HHT.Conclusion: HHT exerts an antimyeloma effect by inducing excess mitophagy, providing new mechanistic insights into a therapeutic strategy for MM.Keywords: homoharringtonine, multiple myeloma, mitophagy, Parkin, mitochondrial dysfunction